1987
DOI: 10.1200/jco.1987.5.1.62
|View full text |Cite
|
Sign up to set email alerts
|

Screening for recurrent breast cancer--its effectiveness and prognostic value.

Abstract: Performance of periodic follow-up examinations after mastectomy for breast cancer is standard practice, primarily for early detection and treatment of recurrence. This study was designed to determine whether this routine screening resulted in significant survival benefit for the patient. The medical records of 1,230 women treated for cure of invasive carcinoma of the breast were reviewed, and 248 cases of recurrence were identified for analysis. Only 36% of recurrences were discovered asymptomatically. Asympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
36
0
7

Year Published

1988
1988
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(45 citation statements)
references
References 9 publications
2
36
0
7
Order By: Relevance
“…The results showed no increase in delay in diagnosing recurrence and reinitiating specialist care as a result of primary care follow-up. As has been reported in previous studies (Clark and Morris, 1981;Hughes, 1985;Tomin and Donegan, 1987;McWhinney et al, 1990;Worster et al, 1995), the results of the RCT (Grunfeld et al, 1996) showed that most recurrences are detected in the interval between regularly scheduled follow-up appointments, and many are presented to the general practitioner irrespective of the formal follow-up arrangements. The results also showed no increase in anxiety or deterioration in health-related quality of life (HRQOL) (Grunfeld et al, 1996).…”
supporting
confidence: 58%
“…The results showed no increase in delay in diagnosing recurrence and reinitiating specialist care as a result of primary care follow-up. As has been reported in previous studies (Clark and Morris, 1981;Hughes, 1985;Tomin and Donegan, 1987;McWhinney et al, 1990;Worster et al, 1995), the results of the RCT (Grunfeld et al, 1996) showed that most recurrences are detected in the interval between regularly scheduled follow-up appointments, and many are presented to the general practitioner irrespective of the formal follow-up arrangements. The results also showed no increase in anxiety or deterioration in health-related quality of life (HRQOL) (Grunfeld et al, 1996).…”
supporting
confidence: 58%
“…One of the main prognostic discriminants is the site and number of metastases, which makes it difficult to compare (inter-) national data deriving from different hospitals. Nevertheless, median post-recurrence survival is mostly in the range of 18-24 months (Powles et al, 1980;Patel et al, 1986;Tomin & Donegan, 1987;Perez et al, 1990;Dixon et al, 1991), which strongly resembles our data (20.3 mo). Almost 60% of the women in the three hospitals had received radiation treatment for advanced disease.…”
Section: Discussionsupporting
confidence: 80%
“…The value of clinical laboratory tests in the follow-up of breast cancer patients has been questioned due to their insensitivity and nonspecificity (Ormiston et al, 1985;Tomin & Donegan, 1987). CEA has been the only tumour marker suitable in some cases for the monitoring of treatment in advanced breast cancer (Tormey & Waalkes, 1978;Mughal et al, 1983).…”
mentioning
confidence: 99%